Formulação de massa cerâmica para revestimento poroso utilizando resíduos de madeiras tropicais - Duarte, Germana de Vasconcelos; Sampaio, Paulo de Tarso Barbosa; Ribeiro, Ruy Alexandre de Sá; Soares, Jose Josimar; Mendonça, Rannier Marques (Ciência Florestal, 2022)
The powder wastes of tropical wood Angelim Rajado (AR) (Pithecelobium racemosum Ducke) and Sucupira Vermelha (SV) (Andira parviflora Ducke), generated in the wood industry in Itacoatiara – Amazonas state, Brazil are usually deposited in inappropriate places. In this work, clay was partially replaced by wastes in the manufacture of ceramic materials to development of a new material for application in porous wall covering (tile) (BIII type), as a sustainable alternative for the Ceramic Pole of the municipality of Iranduba – AM. Specimens (60mm x 20mm x 8mm) were formed by uniaxial pressing (20 MPa) dried at 110ºC per 24h and fired at 750 and 850ºC. The effects of the sintering process on ceramic masses with SV and AR wood wastes were studied by TGA-DSC, XRF (X-Ray Fluorescence) and XRD (X-Ray Diffractometer). After firing, the samples were subjected to the following technological characterizations: water absorption, linear retraction, apparent density, apparent porosity, and modulus of rupture at flexure. The mineralogical and microstructural characteristics were also analyzed. The results show that up to 10% of AR and SV wood wastes in powder form can be incorporated into structural ceramic masses for the production of ceramic materials. However, formulations with 5 and 10% of the SV waste present superior results at the same proportions with AR, being in agreement with the parameters of NBR 13818 (Brazilian Technical Regulation Association).
Formulation ceramic mass for porous coating, using tropical wood wastes
Keywords: Resíduos de madeiras tropicais; Materiais cerâmicos; Propriedades tecnológicas; Alternativa sustentável